Collections of the natural history museum of lille. VIII. Diplostraca (types and figured specimens) - Hennion, Marie (2015)
Fil: Hennion, Marie. Muséum National d’Histoire Naturelle. Département Biologie des Invertébrés Marins et Malacologie; Francia.